Constructivist Approaches: A Budding Paradigm for Teaching and Learning Entrepreneurship Education - NumbaraBari E Kayii; Margaret E Akpomi (International Journal of Education, Teaching, and Social Sciences, 2022)
Constructivism is an approach to learning that believes in the personal construction of knowledge by learners through the interaction of prior knowledge to form a new experience. Constructivism represents the state-of-the-art in the teaching of Mathematics and Sciences at all levels of education. However, there is less work on constructivist teaching and learning in Entrepreneurship Education. This study reviewed theoretical and empirical studies on constructivism with emphasis on how it can help organizations achieve value creation through the vehicle of Entrepreneurship Education. Also, the study summarizes the pedagogical goals of constructivist learning and conceptualizes the dimensions of Entrepreneurship Education, the relevance of Entrepreneurship Education, teaching methods in Business Education, and brings out an understanding of the paradigm shift. The study reveals that the focus of Entrepreneurship Education is to promote innovation and value creation among learners. Consequently, the researcher has drawn a useful conclusion on the application of constructivist approaches in teaching Entrepreneurship Education, and it was recommended, among others; that stable industrial policy on the collaboration between small business entrepreneurs and research institutions for the exploitation of research findings of those institutions to achieve sustainable technological development.